Malay students' entrepreneurial attitude and entrepreneurial efficacy in vocational and technical secondary schools of Malaysia - Lope Pihie, Zaidatol Akmaliah; Bagheri, Afsaneh (Universiti Putra Malaysia Press, 2011)
Entrepreneurial attitude and entrepreneurial self-efficacy are considered as important factors affecting the intention to step into the process of entrepreneurship. However, there is limited information on students' entrepreneurial attitude and entrepreneurial self-efficacy, particularly for technical school students who have acquired the technical knowledge to become entrepreneurs. This study has surveyed entrepreneurial attitude and entrepreneurial self-efficacy among secondary school students in Malaysia. A total of 2,574 students undertaking technical subjects were randomly selected as the participants. A set of questionnaire was employed to measure students' attitudes toward and efficacy in entrepreneurship. Findings of the study indicate that the student scored high on entrepreneurial attitude components including self-esteem cognition, achievement cognition, and achievement affect. However, the students' mean score for entrepreneurial self-efficacy was between moderate to high level. This paper discusses the importance of intervention programmes and proper teaching and learning strategies to improve technical students' entrepreneurial attitude and entrepreneurial self-efficacy.